DAYA HAMBAT MINUMAN PROBIOTIK YOGHURT SUSU SAPI TERHADAP Porphyromonas gingivalis SECARA IN VITRO - Zulfan M. Alibasyah; Diana Setya Ningsih; Siti Fadhilla Ananda (Dentistry Faculty, 2018)
Chronic Periodontitis is one periodontal disease. The main cause of periodontitis chronic disease is bacteria which present in subgingival plaque, that called porphyromonas gingivalis. Chronic periodontitis treatment includes treatment to eliminate pathogenic bacteria such as Porphyromonas gingivalis. Use of probiotics such as yoghurt can be used as s treatment to inhibited pathogenic bacteria because it contains lactic acid bacteria. In this study, uses yoghurt derived from cows milk. This study aims to know the inhibitory from probiotic drinks of yoghurt to Porphyromonas gingivalis in vitro. Cows milk yoghurt is made with adding lactic acid bacteria 2%, 3%, 4%, and 5% concentration. In this research used an agar-well diffusion assay to see inhibited the drink probiotic yoghurt cows milk in Porphyromonas gingivalis. The result was analyzed with one way ANOVA. The result showed there are differences in the inhibition of Porphyromonas gingivalis zone after being exposed to probiotic cows milk yoghurt with concentration 2%, 3%, 4%, and 5% (p0,05). Inhibition zone probiotic drinks of cows milk yoghurt against Porphyromonas gingivalis which made by beginning at probiotic cows milk on the Porphyromonas gingivalis concentration 4% (14,6 mm) and 5% (19,2 mm), both includes as weak category and average according to Ahn classification. The conclusion of this study is probiotic cows milk yoghurt has inhibitory effect againts Porphyromonas gingivalis.Keyword: Chronic periodontitis, Porphyromonas gingivalis, probiotic, cows milk yoghurt.